In‐Plane Anisotropic Thermal Conductivity of Few‐Layered Transition Metal Dichalcogenide Td‐WTe2. Issue 7 (27th December 2018) - Chen, Yu; Peng, Bo; Cong, Chunxiao; Shang, Jingzhi; Wu, Lishu; Yang, Weihuang; Zhou, Jiadong; Yu, Peng; Zhang, Hongbo; Wang, Yanlong; Zou, Chenji; Zhang, Jing; et al.
Abstract: 2D Td‐WTe2 has attracted increasing attention due to its promising applications in spintronic, field‐effect chiral, and high‐efficiency thermoelectric devices. It is known that thermal conductivity plays a crucial role in condensed matter devices, especially in 2D systems where phonons, electrons, and magnons are highly confined and coupled. This work reports the first experimental evidence of in‐plane anisotropic thermal conductivities in suspended Td‐WTe2 samples of different thicknesses, and is also the first demonstration of such anisotropy in 2D transition metal dichalcogenides. The results reveal an obvious anisotropy in the thermal conductivities between the zigzag and armchair axes. The theoretical calculation implies that the in‐plane anisotropy is attributed to the different mean free paths along the two orientations. As thickness decreases, the phonon‐boundary scattering increases faster along the armchair direction, resulting in stronger anisotropy. The findings here are crucial for developing efficient thermal management schemes when engineering thermal‐related applications of a 2D system. Abstract : In‐plane anisotropic thermal conductivities are experimentally demonstrated in suspended Td‐WTe2 of different thicknesses. Theoretical calculation implies that the in‐plane anisotropy is attributed to the different mean free paths along the two orientations. As the thickness decreases, the phonon‐boundary scattering increases faster along the armchair direction, resulting in the stronger anisotropy.